(Schw)Ehre, wem (Schw)Ehre gebührt : Festschrift zur Verabschiedung von Prof. Dr.-Ing. Dr. h.c. Bernhard Heck - Heck, Alexandra [Hrsg.]Seitz, Kurt [Hrsg.]Grombein, Thomas [Hrsg.]Mayer, Michael [Hrsg.]Stövhase, Jan-Moritz [Hrsg.]Sumaya, Hael [Hrsg.]Wampach, Maryse [Hrsg.]Westerhaus, Malte [Hrsg.]Dalheimer, Lisa [Hrsg.]Senger, Philipp [Hrsg.] (Schriftenreihe des Studiengangs Geodäsie und Geoinformatik / Karlsruher Institut für Technologie, Studiengang Geodäsie und Geoinformatik, 2018)
The commemorative publication in honor of Prof. Bernhard Heck contains 41 contributions written by friends, colleagues, co-workers and former PhD-students. The focus of the scientific articles is on Physical and Satellite Geodesy as well as on geodynamics. It reflects the wide range of academic and scientific research activities of Bernhard Heck. The volume is completed by articles about education at the Geodetic Institute of KIT as well as the importance of Geodesy for society.